1995
DOI: 10.1203/00006450-199510000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in Pregnancy: Uterine Blood Flow and Embryonic Development in the Rat

Abstract: The uterine blood flow to individual implantation sites was evaluated in early normal and diabetic rat pregnancy, and related to maternal metabolic state, length of gestation, and embryonic outcome. The aim was to search for a possible coupling between the flow rate and embryonic development. We studied pregnant rats of a malformation-prone Sprague-Dawley strain on gestational d 9, 10, 11, and 12, a time period which roughly corresponds to postconception wk 3-6 in human gestation. The blood flow in the uterus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…It can be speculated that radicals are formed within the embryonic mitochondria, since they are subjected to substrate overload in the diabetic environment. In favor of this hypothesis are the facts that diabetes induces increased uterine blood flow in early rat pregnancy (50), GLUT-1 is not 4. A schematic figure of the rat catalase promoter region (A) and cDNA (B), outlining the differences in DNA sequence between the H a n d U strains.…”
Section: T I N 5 -C T G a C C G A G C T G G C Ta C 5 -C C T G C T Tmentioning
confidence: 79%
“…It can be speculated that radicals are formed within the embryonic mitochondria, since they are subjected to substrate overload in the diabetic environment. In favor of this hypothesis are the facts that diabetes induces increased uterine blood flow in early rat pregnancy (50), GLUT-1 is not 4. A schematic figure of the rat catalase promoter region (A) and cDNA (B), outlining the differences in DNA sequence between the H a n d U strains.…”
Section: T I N 5 -C T G a C C G A G C T G G C Ta C 5 -C C T G C T Tmentioning
confidence: 79%
“…Congenital malformations are induced in early diabetic pregnancy, usually before the 7th gestational week in humans (5). Analysis of the preplacenta (yolk sac) or early placenta in diabetic rats shows an increased blood flow in the uterine and decidual tissues compared with normal pregnant rats (31), thus suggesting that the transfer of compounds between mother and embryo during a teratologically important period of pregnancy may be elevated. We found that the rate of downregulation of Wnt-3a is related to the dose of exogenous RA, and embryos of severely diabetic mice treated with 50 mg/kg RA downregulated Wnt-3a at a rate similar to embryos of nondiabetic mice treated with 100 mg/kg RA.…”
Section: Discussionmentioning
confidence: 99%
“…Blood flow to the uterine and decidual tissues is increased during the early stages of pregnancy in diabetic rats [19], suggesting that retinoic acid could be delivered to developing embryos at an increased concentration under conditions of hyperglycaemia. Retinoic acid in the embryo is synthesised from vitamin A (retinol) obtained from the maternal circulation.…”
Section: Discussionmentioning
confidence: 99%